2022
DOI: 10.1111/ics.12783
|View full text |Cite
|
Sign up to set email alerts
|

An extract of Leontopodium alpinum inhibits catagen development ex vivo and increases hair density in vivo

Abstract: Objectives: Hair loss and reduction in hair volume are hallmarks of hair disorders, such as telogen effluvium, or male or female pattern hair loss, and hair ageing, which can cause severe distress in both men and women. Common antihair loss drugs carry some side effects; therefore, novel, safer approaches targeting milder phenotypes are highly advocated. In this context, we investigated an extract of the alpine plant Edelweiss, Leontopodium alpinum var. Helvetia, for its ability to modulate hair follicle (HF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Apoptotic cells in skin cryosections (7 μm) were assessed by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) according to previously described protocols [37,[42][43][44]. Briefly, the cryosections were fixed in 4% PFA in PBS and then labelled with digoxigenin-deoxy-UTP (ApopTag fluorescein in situ apoptosis detection kit; Merck Millipore, USA) in the presence of terminal deoxynucleotidyl transferase.…”
Section: Immunohistochemistry and Immunofluorescence Microscopymentioning
confidence: 99%
“…Apoptotic cells in skin cryosections (7 μm) were assessed by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) according to previously described protocols [37,[42][43][44]. Briefly, the cryosections were fixed in 4% PFA in PBS and then labelled with digoxigenin-deoxy-UTP (ApopTag fluorescein in situ apoptosis detection kit; Merck Millipore, USA) in the presence of terminal deoxynucleotidyl transferase.…”
Section: Immunohistochemistry and Immunofluorescence Microscopymentioning
confidence: 99%
“…Although both groups had similar treatment outcomes, pumpkin seed oil was identified as a new and safe treatment option. Campiche et al [68] identified the effects of Leontopodium alpinum in regulating hair follicle growth, including inhibition of hair loss in vitro and an increase in hair regrowth in vivo. Nakamura et al [69] discovered that water-soluble peptides from egg yolk, also known as hair growth peptide (HGP), stimulate the production of vascular endothelial growth factor (VEGF) and human dermal papilla cell growth by inducing hypoxia-induced factor (HIF)-1a-mediated transcriptional pathways and VEGF expression.…”
Section: Miscellaneousmentioning
confidence: 99%